Development as transformation : the local church in Lavender Hill as agent of change in a post-Carnegie II context - Bowers, Nadine Francis; August, Karel Th.; Swart, Ignatius (Stellenbosch : University of Stellenbosch, 2011)
Thesis (DTh)--University of Stellenbosch, 2005.